Increased Ankle Plantar Flexor Stiffness Is Associated With Reduced Mechanical Response to Stretch in Adults With CP - Lorentzen, Jakob; Frisk, Rasmus Feld; Nielsen, Jens Bo; Barber, Lee (Frontiers in Bioengineering and Biotechnology, 2021)
Hyperexcitable stretch reflexes are often not present despite of other signs of spasticity in people with brain lesion. Here we looked for evidence that increased resistance to length change of the plantar flexor muscle-fascicles may contribute to a reduction in the stretch reflex response in adults with cerebral palsy (CP). A total of 17 neurologically intact (NI) adults (mean age 36.1; 12 female) and 13 ambulant adults with CP (7 unilateral; mean age 33.1; 5 female) participated in the study. Subjects were seated in a chair with the examined foot attached to a foot plate, which could be moved by a computer-controlled electromotor. An ultrasound probe was placed over the medial aspect of the leg to measure the length of medial gastrocnemius muscle fascicles. Slow (7 deg/s) and fast (200 deg/s) stretches with amplitude 6 deg of the plantar flexors were applied over an ankle range of 70 deg at 10 deg intervals between 60 and 130 deg plantarflexion. It was checked by EMG electrodes that the slow stretches were sufficiently slow not to elicit any activity and that the fast stretches were sufficiently quick to elicit a maximal stretch reflex in both groups. The torque elicited by the stretches was measured together with changes in the length of medial gastrocnemius muscle fascicles. Muscle fascicles increased significantly in length with increasing dorsiflexion position in both populations (p < 0.001), but the fascicles were shorter in the CP population at all positions. Slow stretches elicited significantly larger torque and significantly smaller length change of muscle fascicles as the ankle joint position was moved more towards dorsiflexion in CP than in NI (p < 0.001). Fast stretches elicited larger torque responses at ankle joint positions of 80–100 deg in the NI than in the CP group (p < 0.01). A significant negative correlation was observed between the torque response and muscle fascicle length change to slow stretch in CP (p < 0.05), but not in NI. These findings support that increased passive resistance of the ankle plantar flexor muscle-tendon unit and development of contractures may conceal stretch reflex response in adults with CP. We argue that this should be taken into account in the neurological examination of spasticity.